Analisis Potensi Implementasi Sistem Politik Tanpa Partai di Indonesia dan Dampaknya terhadap Demokrasi dan Tata Kelola Pemerintahan - M. Reza Saputra; Wicipto Setiadi; Ahmad Ahsin Thohari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research analyzes the potential implementation of a non-party political system in Indonesia and its impact on democracy and governance. Indonesia has adopted a multi-party system since the reform era in 1998, but has often faced challenges that threaten the stability and quality of democracy. One of the main issues is the dominance of political parties in the government bureaucracy, which leads to practices of corruption, collusion, and nepotism. This study explores the alternative of a non-party political system as a solution to improve meritocracy, reduce political oligarchy, and strengthen the accountability of public officials. A qualitative approach with a literature study method is used to collect data from various sources. The results show that while a non-party system has the potential to bring positive impacts, constitutional challenges, resistance from political parties, and risks to political diversity remain significant obstacles. Reforming the party system with a focus on transparency, accountability, and cadre quality is considered more realistic and effective in improving democracy and governance in Indonesia.